Acute Necrotizing Encephalopathy: A Rare Complication of H1N1 Infection - Martins,Andreia A. (2018)
Acute necrotizing encephalopathy is a rare complication of H1N1 influenza infection, more prevalent in preschool children. It is characterized by a rapid neurological deterioration with progressive decline on the level of consciousness in the context of a febrile disease, associated with multifocal symmetric brain lesions. The cases of two children (two and four years old) admitted due to an altered level of conscience in the context of febrile respiratory infection are described. The laboratory studies disclosed high aminotransferases with normal ammonia, and the presence of H1N1 virus in the nasopharyngeal swab. The brain computed tomography showed bilateral thalamic hypodensities. The clinical evolution was very distinctive in the two cases, with brain death in one and survival with good neurological outcome in the other. The association of febrile respiratory infection and a rapid decline on the level of consciousness should be an alert to this entity, which has high morbidity and mortality. For the diagnosis, it is recommended to search for the virus in the nasopharyngeal swab. In addition to supportive treatment, oseltamivir and immunomodulators, although controversial, are the most commonly used therapies.